Quand le capitalisme retourne les valeurs de l’éducation - Renaud Hétier (Recherches en Éducation)
Three levels of values can be distinguished in capitalism: the deep (and hidden) values (violence and perversion), the 'human' values (essentially individual freedom) and the functional values (efficiency, progress, competition, etc.) which are regulated by an apparently neutral value : efficiency. In this economic context, education becomes over-education, both through an excessive concern to satisfy the desires of children which today coincide with the inter-ests of the market (digital leisure, in particular), and through an over-investment in the paradigm of 'intelligence', which is being criticised in a new way. In this respect, the solution can probably only come from the longanimity accorded to childhood and an educational withdrawal (Rousseau), from the rebalancing that this should finally allow in favour of sensible, moral and spiritual values. We will then project ourselves into the possibility of the for-mation of a resistant subject, in more ways than one.